Uzbek language as a second language and Uzbek language teaching methods - Sobirova Elgiza Alibek kizi (Лучшие интеллектуальные исследования, 2024)
Abstract: Uzbek language is a very rich and historical language in the world and there are a great deal of people who speak in Uzbek language. A satisfying and rewarding experience, teaching Uzbek as a second language can provide students with an insight into Central Asian civilization and culture. The Turkic language known as Uzbek is predominantly spoken in Uzbekistan, but it is also spoken in some areas of Tajikistan, Kazakhstan, Kyrgyzstan, Afghanistan, and Turkmenistan. The following are some general traits and details of the Uzbek language: